What is the best treatment for seizures in patients with hyponatremia?. Issue 1 (January 2018) - Clauson, Erik R.; Moss, David A.
Abstract : EVIDENCE‐BASED ANSWER : In the setting of severe hyponatremia symptoms, including seizure, the best treatment is an infusion of 3% hypertonic saline until symptoms resolve (SOR: B, based on systematic review of consensus practice guidelines). The rate and volume recommended varies, ranging from continuous infusion to bolus doses, but correction should not exceed 10 mmol/L in the first 24 hours (SOR C, based on consensus guidelines).